Implementing Image-Based Media to Improve Social Studies Learning Outcomes on Indonesia’s Foreign Policy: A Classroom Action Research Study - Deatri, Deatri; Ratnawati, Ratnawati (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to improve students’ Social Studies learning outcomes on the topic of Indonesia’s foreign policy through the implementation of image-based media in an Islamic elementary school classroom. Methodology: This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model. The research involved 25 sixth-grade students. Data were collected using achievement tests, observation sheets, questionnaires, and interviews. Data analysis used descriptive statistics and percentage techniques to evaluate learning outcomes and classroom activities across two research cycles. Main Findings: The results showed that students’ mean scores improved from 38.26 to 65.52 in Cycle I and increased further to 80.50 in Cycle II. The percentage of students achieving the minimum mastery criterion rose from 48% to 60% in Cycle I and reached 92% in Cycle II. Student engagement and participation also improved significantly during the implementation. Novelty/Originality of this study: This study provides a specific application of image-based media in teaching Indonesia’s foreign policy using a Classroom Action Research framework. It offers practical evidence on improving learning outcomes through visual media in Islamic elementary education. The study contributes to contextualized instructional strategies for abstract Social Studies topics at the primary education level.